Snake-Bite in Nepal - Chaudhary, S; Singh, S; Chaudhary, N; Mahato, SK (Journal of Universal College of Medical Sciences, 2014)
Snake-bite is one of the diseases which is included in the World Health Organization's (WHO) list of neglected tropical diseases. It is a well-known life threatening medical emergency commonly seen in farmers, plantation workers, herders, fishermen, snake restaurant workers and other food producers. In Nepal, snake-bite take a heavy toll of human lives. It is due to poor health services in rural areas especially for antisnake venom (ASV) treatment facility. Exact magnitudes of problem and mortality from snake-bite are very difficult to estimate due to serious misreporting. This review article aims to discuss the epidemiology, clinical features, diagnosis, treatment and prevention of snake-bite envenomation in South Asia region particularly in Nepal and helping in improving the knowledge and understanding of snake-bite to save precious human lives. DOI: http://dx.doi.org/10.3126/jucms.v2i3.11829 Journal of Universal College of Medical Sciences Vol.2(3) 2014: 45-53